PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP NILAI PERUSHAAN PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Diana, Diana; David, David; M. Fikri Caesarandi Hasibuan; Mila Afriani (Triwikrama: Jurnal Ilmu Sosial, 2023)
This research aims to determine the effect of profitability, liquidity and leverage on company value in automotive sub-sector companies and their components listed on the Indonesia Stock Exchange in 2015 - 2020. The sample obtained was 9 automotive sub-sector companies and their components listed on the IDX in 2015 - 2020 with a total of 54 observation data over 6 years of observation. The data collection technique used is documentation with data sources using secondary data taken through the official website of the Indonesian Stock Exchange. The data analysis technique used in this research is multiple linear regression analysis using SPSS 26 software. The results of this research show that profitability has a significant effect on company value. Liquidity does not have a significant effect on company value. Leverage affects company value. Then there is the effect of profitability, liquidity and leverage and on company value simultaneously.